2010
DOI: 10.1139/z10-020
|View full text |Cite
|
Sign up to set email alerts
|

Temperature fluctuations affect offspring sex but not morphological, behavioral, or immunological traits in the Northern Painted Turtle (Chrysemys picta)

Abstract: Evolutionary theory predicts that when phenotypic variation arises during development that differently influences the fitness of each sex, selection should favor the maternal ability to match offspring phenotype to the sex that incurs a fitness benefit from that phenotype. In reptiles with temperature-dependent sex determination, the temperatures experienced during incubation can influence numerous phenotypic parameters, including sex. To mimic more naturalistic conditions, this experiment examined how variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…When compared to the thermal responsiveness of other traits, the response is relatively consistent with more female‐biased sex ratios being produced in species with TSD pattern 1a under fluctuating conditions relative to constant temperature treatments of the same mean, and with increasing amplitude of fluctuations (Bull, ; Carter et al., ; Georges, Limpus, & Stoutjesdijk, ; Les et al., ; Paitz et al., ). For example, incubating C. picta eggs at a constant 27.0°C resulted in 100% males while eggs incubated at 27.0 ± 8°C resulted in 100% females despite the fact both conditions had the same mean temperature (Paitz et al., ). While temperature fluctuations typically result in the increased production of females, extreme fluctuations can produce male‐biased sex ratios (Neuwald & Valenzuela, ).…”
Section: Fluctuating Temperature Incubation Studies Are the Future Ofmentioning
confidence: 80%
See 1 more Smart Citation
“…When compared to the thermal responsiveness of other traits, the response is relatively consistent with more female‐biased sex ratios being produced in species with TSD pattern 1a under fluctuating conditions relative to constant temperature treatments of the same mean, and with increasing amplitude of fluctuations (Bull, ; Carter et al., ; Georges, Limpus, & Stoutjesdijk, ; Les et al., ; Paitz et al., ). For example, incubating C. picta eggs at a constant 27.0°C resulted in 100% males while eggs incubated at 27.0 ± 8°C resulted in 100% females despite the fact both conditions had the same mean temperature (Paitz et al., ). While temperature fluctuations typically result in the increased production of females, extreme fluctuations can produce male‐biased sex ratios (Neuwald & Valenzuela, ).…”
Section: Fluctuating Temperature Incubation Studies Are the Future Ofmentioning
confidence: 80%
“…The number of studies on species with TSD using sinusoidal temperature fluctuations in the laboratory are increasing, and the results from these studies clearly indicate that phenotypes are differentially affected by temperature flucutations (Les et al., ; Paitz et al., ). Given that many of these studies also find that sex is a key phenotypic factor that responds differently to constant and fluctuating conditions and is sensitive to estrogens, studies that simultaneously examine these environmental and maternal effects may provide critical information on how TSD operates in nature.…”
Section: Increasing Ecological and Biological Realism: Heat Waves Enmentioning
confidence: 99%
“…Thus, to fully unravel the consequences of the complex thermal inputs experienced by TSD species, the full spectrum of ecologically-relevant temperatures and variation requires investigation. Previous work found that increasing the variance around low (male-producing) or intermediate (mixed-sex) temperatures feminized TSD turtle sex ratios [6], [11], [12], [13]. However, whether a similar variance experienced around high (female-producing) temperature induces females, males, or is lethal remains untested experimentally.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, assays developed to assess this aspect of the immune system should be broadly applicable to all vertebrates, but may require species‐specific optimization. One popular method of assessing the innate immune response in wildlife is the bacteria‐killing assay (BKA) using whole blood or plasma (Matson, Tieleman, & Klasing, ; Paitz, Clairardin, Griffin, Holgersson, & Bowden, ; Palacios, Sparkman, & Bronikowski, ; Schneeberger, Czirjak, & Voigt, ). This assay has clear construct validity and is ecologically relevant because it assesses the ability of an organism to destroy microbes and a greater ability to destroy microbes is almost certainly advantageous (French & Neuman‐Lee, ; Liebl & Martin, ).…”
Section: Introductionmentioning
confidence: 99%